Penerapan Konsep Zero Waste pada Pengelolaan Limbah Produksi Benih Semangka (Citrullus lanatus L.) menjadi Produk Olahan Nata de Cucu Pada Kelompok Tani Mayang Jaya - Kurniasari, Leli; Ermawaty, Netty; Santika, Putri; Adnan, Moch Rosyadi; Kusumawati, Wida; Badriyah, Lailatul; Pradana, Rizki Tri; Riska, Ananda; Mukhlis, Mukhlis (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Horticultural production in East Java continues to increase each year, particularly in strategic commodities such as chili, shallots, and watermelon. Jember Regency, especially the Mayang District, has become a major center of watermelon production with high productivity. Seputih Village, located in the Mayang District, holds significant potential for horticultural cultivation; however, this potential has not been fully utilized, particularly in the processing of waste from seed production such as the flesh of watermelon and chili, which has so far been discarded. This community service activity aimed to increase the economic value of watermelon waste through training in processing it into value-added food products, namely Nata de Cucu. The program was carried out from October to November 2024 in Seputih Village, involving the State Polytechnic of Jember, five students, the Mayang Jaya Farmers Group, and the local community. The implementation method included several stages: preparation, collection of previous research results, program socialization, technology dissemination through training, and monitoring and evaluation. A training module was developed to assist participants in processing watermelon waste independently, even after the program ends. The results of the activity showed a high level of enthusiasm from the partners, especially from the women farmer group. After the training, there was an 80% increase in the knowledge and skills of the farmers in processing watermelon waste into Nata de Cucu, which was then packaged and labeled. The conclusion of this program indicates a positive response and success in adding economic value to agricultural waste. Further action is needed to expand the utilization of watermelon waste not only as a food product but also as a potential source of renewable energy, considering the large volume of waste produced.